Amyloid-β Induces Cdh1-Mediated Rock2 Stabilization Causing Neurodegeneration - Lapresa, Rebeca; Agulla, Jesus; Gonzalez-Guerrero, Sonia; Bolaños, Juan P.; Almeida, Angeles (Frontiers in Pharmacology, 2022)
Alzheimer's disease (AD) is a neurodegenerative disorder characterized by progressive cognitive decline, which is causally related to the accumulation of abnormally folded amyloid-β (Aβ) peptide and hyperphosphorylated tau protein aggregates. The dendritic spine regulator Rho protein kinase 2 (Rock2) accumulates in the brain at the earliest stages of AD and remains increased during disease progression. However, the molecular mechanism that upregulates Rock2 in AD, and its role in the disease progression, are unknown. Here, we found that oligomers of the amyloidogenic fragment 25-35 of the Aβ peptide (Aβ25-35) trigger Rock2 accumulation and activation in mouse cortical neurons in primary culture and in mouse hippocampus in vivo. Neuronal apoptotic death and memory impairment caused by Aβ25-35 administration were rescued by genetic and pharmacological inhibition of Rock2 activity. Mechanistically, Aβ25-35 elicited cyclin dependent kinase-5 (Cdk5)-mediated phosphorylation of Cdh1, a cofactor that is essential for the activity of the E3 ubiquitin ligase anaphase-promoting complex/cyclosome (APC/C) in neurons. Notably, phosphorylated Cdh1 was disassembled from the APC/C complex, causing its inactivation and subsequent Rock2 protein stabilization and activation. Moreover, Aβ25-35-induced neuronal apoptosis was prevented by expressing a phosphodefective form of Cdh1, but not by a phosphomimetic Cdh1. Finally, Cdh1 inactivation, using both genetic and pharmacological approaches, enhanced Aβ25-35-mediated neuronal death through a mechanism that was prevented by inhibition of Rock2 activity. These results indicate that the Cdk5-Cdh1 signaling pathway accounts for the increased Rock2 activity by amyloidogenic Aβ peptides and that this mechanism may contribute to neurodegeneration and memory loss in AD.